ChIP-Seq Peak Calling and Data Analysis in Woody Plants - Lina, Wang (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2018)
Chromatin immunoprecipitation (ChIP) followed by highthroughput sequencing (ChIP-Seq) provides an important tool to study genome-wide protein-DNA interactions to help understand gene regulation in the context of native chromatin. A complete ChIP-Seq workflow including peak calling, peak classification, transcription factor binding site overrepresentation and definition of new TFBS motifs. In this paper, ChIP-Seq peak calling and data analysis is described in detail.